2009
DOI: 10.1016/j.acvd.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Should we close hypoxaemic patent foramen ovale and interatrial shunts on a systematic basis?

Abstract: Hypoxaemic shunts are treated effectively by transcatheter closure, resulting in functional improvement in patients without respiratory insufficiency. When associated with chronic respiratory insufficiency, hypoxaemia often persists after shunt closure. In such cases, the right-to-left atrial shunt does not seem to be the main cause of hypoxaemia and the indication for closure is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…post‐pneumoectomy, abdominal surgery or dilatation of the ascending aorta). Elevation in RA pressure relative to LA pressure will also cause right‐to‐left shunting across the interatrial defect and can occur in cardiac tamponade or conditions that increase right‐sided heart pressures (RV infarction, atresia or stenosis of the pulmonary or tricuspid valve and decrease diastolic compliance of the RV) . We have demonstrated that in our case, shunting occurred without pulmonary hypertension due to decreased diastolic compliance and increased pressures in the right heart (mean RA 10 mmHg, RV end‐diastolic pressure 10 mmHg), equalising the LA pressures (direct LA pressure 14 mmHg).…”
Section: Discussionmentioning
confidence: 63%
“…post‐pneumoectomy, abdominal surgery or dilatation of the ascending aorta). Elevation in RA pressure relative to LA pressure will also cause right‐to‐left shunting across the interatrial defect and can occur in cardiac tamponade or conditions that increase right‐sided heart pressures (RV infarction, atresia or stenosis of the pulmonary or tricuspid valve and decrease diastolic compliance of the RV) . We have demonstrated that in our case, shunting occurred without pulmonary hypertension due to decreased diastolic compliance and increased pressures in the right heart (mean RA 10 mmHg, RV end‐diastolic pressure 10 mmHg), equalising the LA pressures (direct LA pressure 14 mmHg).…”
Section: Discussionmentioning
confidence: 63%
“…Currently, there are no clearly-defined guidelines with reference to PFO management due to the lack of randomised controlled trials comparing the different treatment options 3. There is even less evidence concerning the optimal management of patients with severe hypoxaemia from RLS due to reopening of an FO 9 20. Recent studies suggest that percutaneous closure is an effective treatment in hypoxemic shunts with functional improvement of the patients and resolution of acute respiratory failure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Several small molecule inhibitors and radiotherapy in the abdomen and lower extremities have been linked with accelerated progression of PAD, especially in those patients with underlying preexisting cardiovascular risk factors [55][56][57][58]. Nilotinib and ponatinib-two tyrosine kinase inhibitors used for the treatment of Philadelphia chromosome-positive chronic myelocytic leukemia-have been associated with rapidly progressive peripheral atherosclerosis, sometimes resulting in early termination of crucial therapy [58,59].…”
Section: Peripheral Artery Disease From Vasculotoxic Therapiesmentioning
confidence: 99%